2017
DOI: 10.1371/journal.pone.0178261
|View full text |Cite
|
Sign up to set email alerts
|

Research data management in academic institutions: A scoping review

Abstract: ObjectiveThe purpose of this study is to describe the volume, topics, and methodological nature of the existing research literature on research data management in academic institutions.Materials and methodsWe conducted a scoping review by searching forty literature databases encompassing a broad range of disciplines from inception to April 2016. We included all study types and data extracted on study design, discipline, data collection tools, and phase of the research data lifecycle.ResultsWe included 301 arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 23 publications
0
49
0
Order By: Relevance
“…The articles referenced above and many others share a method of grouping stakeholders by professional or institutional identity. Perrier et al (2017), for instance, divide stakeholders into professional groups (researchers, administrators, participants, and funders) in their survey of research data management (p. 9). Another formulation of stakeholders is possible, in that those who work in scholarly communications could define themselves by the metadata roles they have in common.…”
Section: Methodsmentioning
confidence: 99%
“…The articles referenced above and many others share a method of grouping stakeholders by professional or institutional identity. Perrier et al (2017), for instance, divide stakeholders into professional groups (researchers, administrators, participants, and funders) in their survey of research data management (p. 9). Another formulation of stakeholders is possible, in that those who work in scholarly communications could define themselves by the metadata roles they have in common.…”
Section: Methodsmentioning
confidence: 99%
“…The collection method does not guarantee completeness, which means there might be research data lifecycle models not captured by our analysis. Since [2] already provides a scoping review of the relevant literature this is an acceptable Figure 1: Publication types of found research data management models/lifecycles defect. Our approach was focused on finding criteria to compare data lifecycle models to each other and to evaluate the fitness of lifecycle models in general for certain purposes, which does not necessitate completeness.…”
Section: Threats To Validitymentioning
confidence: 99%
“…Most of these models break down the phenomena of research data management into a series of tasks or states of data and relate them to different roles or actors. As [2] indicates, these models are often not evaluated in a manner that allows to reproducibly derive the same model for a certain purpose (explaining, educating, etc.). A model un-evaluated is, scientifically speaking, of doubtful quality.…”
mentioning
confidence: 99%
“…While useful tools for assessing needs for institutional research data services, they lack a mechanism to collect feedback on researchers' current practices for these treatments and assessment of their satisfaction for these treatments. A scoping review of 310 articles by Perrier et al (2017) found that most research data management studies performed by academic institutions do not include direct interaction with data producers but instead rely on indirect methods such as self-reporting surveys and case studies by a third-party observer. Jahnke, Asher, and Keralis's 2012 CLIR study, however, does approach researcher attitudes directly via their method of ethnographic interviews with social sciences researchers at five institutions.…”
Section: Literature Reviewmentioning
confidence: 99%